Quality of Life for Students with Intellectual Disabilities and Kingdom’s Vision 2030 - Hamoud Bin Abdullah Al-Moghyrah (الآداب)
The article aims to study the quality of life for students with intellectual disabilities in light of the Kingdom's Vision 2030, as there is an increasing need to improve the quality of life for their in the educational environment, and quality education promotes learners' well-being and contributors to their success. This article focuses on the role of Universal Design for Learning (UDL) in enhancing the quality of life for this group, in line with Saudi Arabia’s Vision 2030. The Vision 2030 policy and the social model of disability were analyzed, and several conclusions were drawn based on documents that meet inclusion standards. The study's findings indicate that the "Quality of Life" and "Human Capability Development" programs support students with intellectual disabilities. UDL improves students' access to the curriculum and contributes to achieving its objectives, aligning with the Kingdom’s vision for inclusive education. The study recommends adapting the national curriculum and developing infrastructure in accordance with UDL principles, in addition to fostering international cooperation to leverage successful experiences in this field.